Discontinuation Patterns and Cost Avoidance of a Pharmacist-Driven Methicillin-Resistant Staphylococcus aureus Nasal Polymerase Chain Reaction Testing Protocol for De-escalation of Empiric Vancomycin for Suspected Pneumonia. (4th March 2021) - Meng, L; Pourali, S; Hitchcock, M M; Ha, D R; Mui, E; Alegria, W; Fox, E; Diep, C; Swayngim, R; Chang, A; Banaei, N; Deresinski, S; et al.
Abstract: A pharmacist-driven methicillin-resistant Staphylococcus aureus (MRSA) nasal polymerase chain reaction (PCR)-based testing protocol with a 70% acceptance rate for vancomycin discontinuation within 24 hours of negative results significantly reduced unnecessary vancomycin use with an estimated cost avoidance of 40 per vancomycin course. We found high concordance (141 of 147, 96%) of culture-based versus PCR-based MRSA nasal screening.